Correlation between structural, cation distribution with dielectric spectra and magnetic properties for Co–Zn ferrite doped with La3+ ions. (1st May 2023) - Altarawneh, Aseel M.; Arrasheed, Enas A.; Ajlouni, Abdul-Wali; Ghazy, R.; Hemeda, O.M.; Henaish, A.M.A.; Mostafa, M.
Abstract: A series of Co0.65 Zn0.35 Lax Fe2-x O4 was prepared by flash method, where x = 0, 0.02, 0.04, 0.06, 0.08, and 0.1 and was annealed at 800 °C for 2 hrs.The purity of phase structure was confirmed by x-ray diffraction. The dielectric properties were measured and were found that both dielectric constants, ε ′, and ε″, drastically decay in the low-frequency region, up to 50 Hz, and then present an independent pattern in the other part of the frequency range up to 10 7  Hz. The dielectric relaxation in the ferrites was governed by the electron hopping between divalent (Co 2+ ↔ Co 3+ ) and trivalent (Fe 2+ ↔ Fe 3+ ) cations. The Cole-Cole plots show a two-relaxation type explained by the presence of multi-semicircles varying upon the presence of the double relaxation effects associated with grain and grain boundary. The hysteresis loops revealed that by introducing lanthanum ion in the ferrite system, some deviations occur in the system from soft magnetic to hard magnetic properties. We can control the saturation magnetization of the ferromagnetic system just by adding a suitable amount of lanthanum content. Hence, the lanthanum ions substitution has greatly influenced the magnetic properties of Co–Zn ferrite nanoparticles. The initial magnetic permeability ( μ i ) is dependent on the temperature and was measured at different frequencies of 10 kHz, 50 kHz, and 100 kHz of the sinusoidal wave. The maximum amount of heat energy was found to x = 0 sample (CoZn ferrite), the doping with La +3 ion leads to the reduction of the intensity of exothermic peak it may be attributed to La Oxide La–O bond which requires a higher quantity of energy for exothermal. The La addition improves the resistance of the material, so these ferrites could be used for radio applications. The high values of initial permeability in the samples is very beneficial in many applications that required lower dielectric loss and more controllable magnetic losses.